Sensitivity and specificity of cell block method of transthoracic fine needle aspiration in diagnosis of lung cancer - Sutanto, Yusup Subagio; Santi, Nur; Wasita, Brian; Rima, Ana; Kurniawan, Hendra (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundLung cancer is still the main cause of cancer deaths. The high lung cancer mortality rate is caused by a diagnosis factor or therapy selection. The cell block cytology technique using fine needle aspiration (FNA) samples can provide immunocytochemical material that plays an important role in the differential diagnosis of lung cancer subtypes and in determining immunotherapy administration. This study aimed to determine the sensitivity and specificity of transthoracic FNA (TTFNA) cell block cytology in comparison with bronchial washing smears and TTFNA smears in diagnosing lung cancer. MethodsThis was a cross-sectional diagnostic study involving 26 subjects. All subjects had undergone bronchial washing and CT scan-guided fine needle aspiration followed by cell block preparation. Both direct FNA smears and cell blocks are useful in the diagnostic work-up of patients. Comparative statistical analysis of TTFNA cell block versus bronchial washing smear and TTFNA smear cytology was carried out using the McNemar test. ResultsLung cancer was found in 15 patients (57.7%) using the TTFNA cell block technique. The sensitivity and specificity of the TTFNA cell block technique were 85.7% and 75%, respectively. There was no difference in the positivity value between TTFNA cell block technique of bronchial wash smear technique, and TTFNA smear on lung cancer diagnosis (p>0.05). ConclusionsTransthoracic fine-needle aspiration in combination with the cell block technique has good sensitivity and specificity. The TTFNA can be used for immunocytochemical examinations in lung cancer diagnosis and therapy. This approach is valuable for providing individualized treatment and prognostic evaluations.